Akselerasi Kemampuan Membaca Al-Qur’an Melalui Metode Qur’ani Sidogiri - Wasik Wasik; Mat Sari; Mohammad Usman; Hamim Zdulqornain Shofa (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
The problem in this research is about the process of accelerating the ability to read the Qur'an, the results to the supporting and inhibiting factors in accelerating the ability to read the Qur'an through the Qur'anic Sidogiri method in langgar al-maryam blu'uran village and langgar al-Qur'an. falah tlambah village coral penang sampang. To solve this problem, the researcher uses a qualitative approach with a phenomenological type. The location of the research is in langgar al-maryam, blu'uran village and langgar al-falah, tlambah coral village, penang sampang with data collection through observation, interviews, and documentation. While the data analysis was carried out during the research process and after the research took place with an inductive analysis model in reducing data, presenting data and analyzing data. In the results of the research conducted by the teacher of langgar al-maryam, blu'uran village, coral penang sampang and langgar al-falah in accelerating the ability to read the al-qur'an through question and answer, observing, to collecting data, associating and communicating the results. While the results were violated by al-Maryam after using the Qur'anic Sidogiri method, it had begun to develop and all the procedures directed by the Sidogiri Qur'anic method team were carried out well. Meanwhile, in Vital al-Falah, the village of Tlambah Karang, Penang, Sampang saw the results after using the Qur'an;'ani Sidogiri method, it was also proven that students after completing Juz 5 could be sure to be able to read the Qur'an properly in accordance with the rules of the science of tajwid. The factors that support the acceleration of the ability to read the Qur'an are violated by al-Maryam in addition to practical methods, as well as teacher certification because there are senior teachers who are very competent and hard working, and an environment that is still thick with religious knowledge. Meanwhile, in violation of al-falah the teacher's persistence in providing.